Analisis Manajemen Risiko Keselamatan dan Kesehatan Kerja dengan Metode Hazard Analysis (Studi Kasus pada Proyek Pembangunan Rumah Susun BPK RI) - Rizki Gobel; Mohammad Yusuf Tuloli; Arfan Usman Sumaga (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
Occupational Health and Safety (OHS) is a crucial aspect of construction project management to minimize the risk of work-related accidents that may hinder project completion. This study aims to analyze, evaluate, and design a risk management model using the Hazard Analysis Method. The research was conducted through literature studies and direct observations to identify existing risk variables. Data testing employed validity and reliability tests to ensure response consistency, where an R calculated value of ≥ 0.6 indicated high reliability. Once valid and consistent data were obtained, the analysis was carried out using a risk matrix to determine the probability and impact levels of risks. The findings indicate that workplace accidents in construction projects can be classified based on resource categories with varying risk levels. The implementation of OHS policies, regular training, and scheduled supervision has proven effective in reducing the risk of work-related accidents. Therefore, proper OHS risk management can enhance workplace safety and improve the efficiency of construction projects.